Withdrawal response in healthy adults - Chew, K.S.; Oon, L.K.; Lee, R.A.; Lim, K.S.; Tan, C.T. (Asean Neurological Assoc, 2010)
Background: Withdrawal response was used to explain extensor plantar response in population without pyramidal dysfunction but there is lack of data characterizing this response in normal population. Objective: To characterize withdrawal response from pain and tickle sensation in population without any neurological deficit. Methods: The study was carried out using four different stimuli, namely heat-induced pain, cold-induced pain, electric-induced pain using electromyography stimulator and ticklish sensation using superworm (Zophobas morio), applied to normal subjects in University Malaya Medical Centre, Kuala Lumpur. Results: Heat-induced pain resulted in flexion of the big toe (61.1%), other toes (62.3%), ankle dorsiflexion (82.6%), knee flexion (83.9%) and hip flexion (83.9%). Electric-induced pain showed flexion of the big toe (27.7%), other toes (28.3%), ankle dorsiflexion (51.0%), knee flexion (76.0%) and hip flexion (76.0%). Ticklish sensation showed flexion of the big toe (14.8%), other toes (14.8%), ankle dorsiflexion (22.7%), knee flexion (21.9%), and hip flexion (21.9%). There was significant correlation between fear and ticklish sensation induced withdrawal responses and extension of big toe. Cold induced pain resulting in big toe flexion (6.4%), other toes (6.9%), dorsiflexion of ankle (7.1%), flexion of knee (6.9%), and hip flexion (6.9%). Females were more responsive to heat, males to electrical stimulation. The prevalence of big toe extension ranged from 11.0% (electrical), 6.3% (ticklish), 4.8 (heat), to 0% (cold), a mean of 5.2% overall. Conclusion: Withdrawal response caused by nociceptive and ticklish sensation consists mostly of big toe flexion and of other toes, ankle dorsiflexion and flexion of the knee and hip. Extension of the big toe is seen in about 5% of all the stimulation.